Program Rehabilitasi ODGJ melalui Terapi Spiritual di Pondok Pesantren X - Fatimatuz Zahroh; Dewi Mulyani (Jurnal Riset Pendidikan Agama Islam, 2022)
Abstract. This research has background that The Islamic School of X has a program to recovery Soul Disorder People (ODGJ) by spiritual therapy that gives medication to soul disorder patients and drug abuse victim by spiritual therapy such as dzikr and giving a shower. The aims of this research are to know : (1) Rehabilitation program of ODGJ in Dormitory of Islamic School X. (2) Rehabilitation process which is done in Dormitory of Islamic School X. (3) Evaluation in rehabilitation of ODGJ in Dormitory of Islamic School X. (4) The obstacles or the problems in rehabilitation of ODGJ in Dormitory of Islamic School X. This research is using descriptive method through cualitative approachment to research rehabilitation program of ODGJ through spiritual therapy in Dormitory of islamic School X. The data collections in this research are using observation, interview, and documentation,. The technique of analysis data in this research is using analysis data Miles and Huberman model. The result of this research is approving that : (1) Rehabilitation program of ODGJ by spiritual therapy through Dzikr and Sholawat (giving praises to Prophet Muhammad SAW). (2) Rehabilitation process which is done by some procedurs and activities. (3) The result of evaluation such as compatibility of schedule implementation, feedback from the patients, public and family responses about the patients recovery. (4) The obstacles or the problems which are found : the lack of food supply, places, and the keepers of ODGJ. Abstrak. Penelitian ini dilatarbelakangi oleh Pondok Pesantren X yang membuka program rehabilitasi dengan terapi spiritual yang memberikan perawatan dan pengobatan pada pasien gangguan jiwa dan korban penyalahgunaan narkoba melalui terapi spiritual berupa dzikir dan mandi. Tujuan dari penelitian ini adalah untuk mengetahui: (1) program rehabilitasi ODGJ di Pondok Pesantren X. (2) proses rehabilitasi yang dilakukan di Pondok Pesantren X. (3) evaluasi dalam rehabilitasi ODGJ di Pondok Pesantren X. (4) hambatan atau tantangan dalam rehabilitasi ODGJ di Pondok Pesantren X. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif untuk meneliti program rehabilitasi ODGJ melalui terapi spiritual di Pondok Pesantren X. Pengumpulan data pada penelitian ini menggunakan observasi, wawancara, dan dokumentasi. Teknik analis data yang digunakan dalam penelitian ini menggunakan analisis data model Miles dan Huberman. Hasil penelitian menunjukkan bahwa: (1) Program rehabilitasi ODGJ berupa terapi spiritual dengan dzikir dan solawat. (2) Proses rehabilitasi dilakukan melalui beberapa prosedur dan kegiatan. (3) Hasil evaluasi berupa kesesuaian pelaksaan jadwal, feedback dari para pasien, dan tanggapan masyarakat serta keluarga mengenai kesembuhan pasien. (4) Hambatan atau tantangan yang ditemui yaitu kurangnya ketersediaan makanan, kurangnya ketersediaan tempat, dan kurangnya pengurus ODGJ.